“PENGARUH PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA SENTRA PONSEL, PLAZA SIMPANG LIMA, SEMARANG” - Adhi Putra Mahardika, 13.05.51.0167; Yulianto, Heru (Students' Journal of Economic and Management, 2018)
The issues raised are whether the promotion factor and the quality of service to the purchasing decision in Sentra ponsel, Semarang. The purpose of the study was to analyze the influence of promotion, quality of service on purchasing decisions. A sample of 100 respondents, using anon-probability sampling technique withthe sampling method used is purposive sampling, its sampling with the criteria that the respondentisan adult and has been making purchases online. Methods of research data analysis using linear regression. The test results showed that there are positive and significant effect between the promotion on purchasing decisions. there are significant positive and significant correlation between quality of service in purchasing decisions.Keyword :promotion, quality of service, and purchasing decisions